2018
DOI: 10.1002/clc.23138
|View full text |Cite
|
Sign up to set email alerts
|

B‐type natriuretic peptide is associated with remodeling and exercise capacity after transcatheter aortic valve replacement for aortic stenosis

Abstract: Background We aimed to assess longitudinal changes of B‐type natriuretic peptide (BNP) in aortic stenosis (AS) patients treated by transcatheter aortic valve replacement (TAVR). Methods From our TAVR database, we identified 193 consecutive patients with severe symptomatic AS who underwent TAVR and were prospectively followed using serial BNP levels and echocardiography. Patients were divided into subgroups according to type of left ventricular (LV) remodeling as having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
9
0
1
Order By: Relevance
“…The BNP population had a mean age of 61 years and 42% were male, whereas the mean age of participants in the NT-proBNP population was higher at 78 years and 57% were male. All-cause mortality was reported in 21 of the BNP studies [6][7][8][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and the remaining studies reported major adverse cardiovascular events (MACE) [34][35][36][37][38]. The vast majority found that BNP had a significant association with all-cause mortality, with an average threefold increase in death on increasing levels of BNP.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…The BNP population had a mean age of 61 years and 42% were male, whereas the mean age of participants in the NT-proBNP population was higher at 78 years and 57% were male. All-cause mortality was reported in 21 of the BNP studies [6][7][8][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and the remaining studies reported major adverse cardiovascular events (MACE) [34][35][36][37][38]. The vast majority found that BNP had a significant association with all-cause mortality, with an average threefold increase in death on increasing levels of BNP.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%
“…Interestingly, in our study, the post-TAVR serum BNP was significantly associated with residual PVL and MR as well as with higher PHT and lower EF, all of which were previously implicated to be associated with elevated BNP serum levels and worse prognosis [56-58]. It seems that post-procedural serum BNP may incorporate several post-TAVR residual hemodynamic known prognostic post-TAVR parameters [24, 48, 59, 60], each by itself reflecting the combined hemodynamic prognostic profile, and all of which elevated post-TAVR serum BNP levels.…”
Section: Discussionmentioning
confidence: 70%
“…BNP is noted for its short 20-min half-life time [15, 47]. While serum BNP levels were evaluated for short-term outcomes [30-32, 46, 48] and long-term outcomes [34, 49] following TAVR, the majority of these studies were based on pre-procedural admission BNP levels [30-32, 34, 46, 48, 49]. There are limited data evaluating BNP levels post-TAVR at both post-TAVR prior to discharge [33] as well as at 30-day post-TAVR [34, 49].…”
Section: Discussionmentioning
confidence: 99%
“…As the indication of TAVR extended, increasing studies were performed to find the predictor of long-term prognosis. However, limited biomarkers were proposed as a predicting long-term outcome [ 2 , 3 , 26 ]. In the present study, we found altered metabolites responding to TAVR in the peripheral vein in 1 day, 3 days, and 7 days after TAVR could reflect LVM regression.…”
Section: Discussionmentioning
confidence: 99%